2022
DOI: 10.3390/challe13020057
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Knowledge, Attitudes, and Practices of Healthcare Professionals toward Climate Change and Health in Minnesota

Abstract: Climate change is an urgent public health issue that is impacting health locally and across the world. Healthcare professionals are on the front lines for public health, caring for people affected by climate change; yet few studies have assessed their knowledge and experiences of local climate change effects. The purpose of this study was to improve our understanding of the health impacts of climate change in Minnesota from the perspective of healthcare professionals. An electronic survey was administered by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…One of the most commonly cited barriers to counseling patients in both this study and others 15 was lack of time during the clinical encounter. A study analyzing records of primary care visits from 1998-2000 found the average duration of a clinical encounter was 17.4 minutes, 48 and despite the increased medical complexity of patients, and increased number of quality measures physicians are now expected to cover compared to 20 years ago, the average duration of a primary care visit based on 2017 data was only 18 minutes.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…One of the most commonly cited barriers to counseling patients in both this study and others 15 was lack of time during the clinical encounter. A study analyzing records of primary care visits from 1998-2000 found the average duration of a clinical encounter was 17.4 minutes, 48 and despite the increased medical complexity of patients, and increased number of quality measures physicians are now expected to cover compared to 20 years ago, the average duration of a primary care visit based on 2017 data was only 18 minutes.…”
Section: Discussionmentioning
confidence: 77%
“…9 While interprofessional health students and clinicians recognize that environmental exposures and climate change are impacting the health of their patients, [10][11][12][13] they cite a lack of education on these topics as a primary barrier to counseling patients. 14,15 In published literature, several frameworks [16][17][18] and curricula have been developed for educating learners (de ned for the scope of this paper to include medical students, residents, fellows, nursing students, and advanced practice provider students) [19][20][21] and clinicians (de ned for the scope of this paper as physicians, nurses, and advanced practice providers) 22 on health impacts of environmental factors in a didactic setting. However, only a few studies have evaluated curricula that speci cally address how learners and clinicians should approach a clinical encounter with an at-risk patient.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of nurses’ awareness of environmental sustainability have revealed that nurses exhibit moderate levels of awareness and a considerable degree of concern regarding the health impacts of climate change [ 37 , 42 , 43 ], as reflected in the NEAT-es results.…”
Section: Discussionmentioning
confidence: 99%
“…It is important for health care professionals to recognize the potential impacts that environmental disruptions can have on women during pregnancy so that appropriate teaching and safety measures can be put in place. The mental health impacts of climate change may be particularly overlooked by health care providers who do not recognize the risks or know how to respond 4 . Birth professionals have an important role to play to ensure that mental health and well‐being are emphasized in this increasingly climate‐changed era.…”
Section: Introductionmentioning
confidence: 99%
“…The mental health impacts of climate change may be particularly overlooked by health care providers who do not recognize the risks or know how to respond. 4 Birth professionals have an important role to play to ensure that mental health and well-being are emphasized in this increasingly climate-changed era.…”
Section: Introductionmentioning
confidence: 99%